Homeostatic pockets of interferon lambda-stimulated gene production in the intestine are associated with localized exposure to bacterial microbiota - David A. Constant; Jacob A. Van Winkle; Kimberly A. Meyer; Shelby R. Madden; Bryan Ramirez Reyes; Timothy J. Nice (Gut Microbes)
Tolerance of enteric microbiota and clearance of potential pathogens is critical for gut homeostasis. We previously found that the healthy small intestine of mice contains discrete pockets of antiviral gene expression that depend on bacterial microbiota colonization and interferon lambda (IFN-λ) receptor expression by intestinal epithelial cells. We now use spatial transcriptomic profiling of homeostatic interferon response pockets to show that they contain a broader cytokine signature that is consistent with activation of innate immune sensors, including toll-like receptors (TLRs). Additionally, we find that these homeostatic innate immune responses are associated with increased local abundance of luminal bacteria, but not with particular bacterial species or overt defects in the epithelial barrier. We find that deficiency of the TLR adaptor MyD88 in hematopoietic cells significantly reduces the abundance of homeostatic innate immune pockets, and stimulation with the bacterial product lipopolysaccharide preferentially stimulates IFN-λ production by intestinal immune cells. We propose that localized increases in proximity of bacterial microbiota to intestinal epithelium result in increased homeostatic uptake of TLR ligands, which stimulates resident immune cells to produce cytokines, including IFN-λ. These localized innate immune responses enhance the immunological barrier, maintaining homeostasis with beneficial microbes and protecting against potential occult pathogens that may be present among the luminal microflora.